The impact of COVID-19 quarantine on lifestyle indicators in the United Arab Emirates - AlBlooshi, Sharifa; AlFalasi, Maryam; Taha, Zainab; El Ktaibi, Farid; Khalid, Alia (Frontiers in Public Health, 2023)
Introduction COVID-19 is a virus that has spread rapidly and brought economic and social crises all around the world. The current study aimed to investigate the impact of COVID-19 quarantine on dietary habits, physical activity, food purchasing, smoking, and sleeping patterns in the United Arab Emirates. Methods A cross-sectional study was conducted using an online questionnaire between November 1st, 2020 and the end of January 2021. Citizens and residents of the UAE aged ≥ 18 years old were asked to complete an anonymous electronic questionnaire created via Google Forms and distributed on various platforms, such as WhatsApp, Twitter, and email. A total of 1682 subjects participated in the study. Results The results included that during the COVID-19 lockdown, more participants (44.4%) reported an increase in weight. This gain seems to be linked to increased food consumption [(Adjusted Odd Ratio) AOR = 1.68, 95% (Confidence Interval) CI = 1.12, 2.54, p = 0.022], decreased physical activity (AOR = 2.25, 95% CI = 1.58, 3.21, p < 0.001), and increased smoking (AOR = 1.90, 95% CI = 1.04, 3.50, p = 0.038). The groups that were most likely to gain weight included those who consumed more cereals (AOR = 1.67, 95% CI = 1.08, 2.57, p = 0.011), had an increased desire for sweets (AOR = 2.19, 95% CI = 1.50, 3.19, p < 0.001), and an increased desire for food (hunger) (AOR = 2.19, 95% CI = 1.53, 3.14, p < 0.001). In contrast, those who exercised more were more likely to lose weight (AOR = 0.61, 95% CI = 0.44, 0.86, p < 0.001) as well as those who slept over 9 h a day (AOR = 1.90, 95% CI = 0.45, 0.88, p = 0.006). Discussion Overall, it is essential to promote healthy habits and methods of healthy diet maintenance during stressful and unusual times when people might find it difficult to put effort into their health.